PENERAPAN METODE PEMBELAJARAN DEEP LEARNING BERBASIS FREKUENSI UNTUK MENINGKATKAN PENGETAHUAN SISWA PADA KONSEP VIRUS DI SMA NEGERI 1 CIBINONG - Gilang Medal Pangrestu; Hendro Prasetyono (STKIP Subang, 2025)
This study aims to investigate the implementation of the frequency-based Deep Learning instructional method to improve students’ knowledge of the virus concept at SMA Negeri 1 Cibinong. The research employed a pre-experimental method with a one-group pretest–posttest design, involving 36 tenth-grade students of SMA Negeri 1 Cibinong as research subjects. The research instrument was a concept knowledge test on viruses administered before and after the learning intervention. The results showed an increase in the average score from 57.11 in the pretest to 84.33 in the posttest, with an N-Gain value of 0.63, which falls into the medium–high category. Thus, it can be concluded that the implementation of the frequency-based Deep Learning method is effective in enhancing students’ knowledge and conceptual understanding of biology material, particularly the concept of viruses.